The Role of Teachers as Assessors and Mentors in Developing the Potential of MI/SD Students - Gita Oktafryani; Cah Ayu Tihuri; Tri Mutia; Abdurrahmansyah Abdurrahmansyah (Peneliti.net, 2026)
This article discusses the role of teachers as assessors and mentors in developing the potential of students in Madrasah Ibtidaiyah (MI) or elementary schools (SD). Teachers function not only as transmitters of knowledge but also as facilitators, motivators, evaluators, and agents of change who play a crucial role in shaping students’ learning independence, motivation, and religious character. This study employs a literature review method with a descriptive qualitative approach to examine relevant literature concerning the role of teachers in enhancing students’ cognitive and affective potential. The findings indicate that the integration of teachers’ roles as mentors and assessors can create a holistic learning process in which students develop intellectually, emotionally, socially, and spiritually. Therefore, teachers serve as key architects in shaping a generation that is intelligent, independent, and morally upright in accordance with the demands of contemporary education.